Kreativitas Mahasiswa Fisika dalam Mendesain Produk Materi Medan dan Gaya Magnet - Nurkhoerudin, Diky; Edie, Sukiswo Supeni; Hartono, Hartono (UPEJ Unnes Physics Education Journal, 2019)
This research aims to know the students ' creativity and factors influencing creativity. The data used in this study that is the result of a creative product evaluation form design and interview. Data analysis techniques used to use a descriptive quantitative analysis approach. The results of data analysis it was concluded that the creativity of the students in physics are divided into three categories, namely high, medium, low details: creativity category "high" with a percentage of 70.34%, the category of "medium" has a percentage of 66.12% and category low percentage of 62.58%. The creativity of the students in physics belongs to the category of "medium" with a percentage score an average of 66.61%. Factors that influence students creativity in physics that is intrinsic motivation and extrinsic motivation, where the students tend to have more intrinsic motivation extrinsic motivation compared with the dominant percentage: intrinsic motivation 50.56%, extrinsic motivation 49.44%.